2013
DOI: 10.1007/s10877-013-9516-8
|View full text |Cite
|
Sign up to set email alerts
|

End-tidal versus manually-controlled low-flow anaesthesia

Abstract: During low-flow manually-controlled anaesthesia (MCA) the anaesthetist needs constantly adjust end-tidal oxygen (EtO2) and anaesthetic concentrations (EtAA) to assure an adequate and safe anaesthesia. Recently introduced anaesthetic machines can automatically maintain those variables at target values, avoiding the burden on the anaesthetist. End-tidal-controlled anaesthesia (EtCA) and MCA provided by the same anaesthetic machine under the same fresh gas flow were compared. Eighty patients were prospectively ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…Moreover, the authors demonstrated no differences in the time to eye opening and extubation between automated and manual methods. Otherwise, the results published by Lucangelo et al [8] are contrary to our data. Lucangelo et al demonstrated that the required concentration of inhalational anaesthetic was achieved more rapidly in the group with manual control.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, the authors demonstrated no differences in the time to eye opening and extubation between automated and manual methods. Otherwise, the results published by Lucangelo et al [8] are contrary to our data. Lucangelo et al demonstrated that the required concentration of inhalational anaesthetic was achieved more rapidly in the group with manual control.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results have been presented by other researchers [6][7][8][9]. In his 10-year observation, Kennedy et al [9] found that automated control of inhalational anaesthetic substantially decreased the additional burden on the anaesthetist and potentially increased the safety of anaesthetised patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…New anesthetic machines; Drager Zeus, GE Aisys, and Maquet flow-I, incorporated a closed loop system, in which the target end-tidal anesthetic concentration, minimum flow rate, and target end-tidal oxygen concentration (EtO2) are set, then the machine automatically modifies inspired agent and fio2 to maintain end-tidal concentrations determined by the anesthesiologist. This is assumed to lower anesthetic gases consump-tion with more stable brain concentration resulting in less required anesthesiologist interventions to modify either inhaled anesthetic or oxygen concentrations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies that investigated EtC were conducted for relatively short period surgeries and non-homogenous patients [6,[8][9][10][11][12]. In our study, we applied EtC mode (Aisys CS2 anesthesia delivery systems, USA) during living donor right hepatectomy where the average anesthetic duration is around 6 h [7,13].…”
Section: Introductionmentioning
confidence: 99%